Solarium Reimagined: Containing the Rise of China (Department of International Relations, Universitas Brawijaya, 2022)
The following paper studies the nature and plausible justifications to current trade war between the US and China. The theory of hegemonic power runs through the narrative embodied in this paper and postulates that the trade war has been initiated as an instrument to counter the rise of China in the global political economy. The lineages of the trade war can be traced back to trade deficit between China and the US, rivalry for global economic dominance and the US midterm elections. This paper will unpack the nature of the trade war looking at the history of other trade wars before this one. The second part will engage international relations theory, particularly hegemonic power and status to examine the validity of the idea that the rise of China threatens to the US national interests and security. The third part will reflect on the above, revisit a project Solarium that president Eisenhower formulated in 1953 to counter the soviet expansionism during the Cold War era and postulate what could be expected next through the prism of hegemonic power in global politics. This paper concludes with an empirical case for caution that just as project solarium was a long-term strategy to counter the soviet expansionism during the Cold War, the US will need a similar long term policy position to counter the Rise of China.